Youth Deradicalization Through Educational Institutions: Philosophical Perspective - Biyanto Biyanto (Universitas Muhammadiyah Malang, 2023)
This article aims to discuss the deradicalization of youths and the important position of educational institutions. The perspective used in this paper is the philosophy of ideological criticism of Jurgen Hubermas. This analysis is used to examine more deeply the ideology and character of the radicalism movement and deradicalization programs carried out by various elements of the nation. By critiquing ideology, we can understand the background of the emergence of radicalism. We can also analyze all forms of expression of resistance to the ideology of radicalism through deradicalization programs, especially through youths. Youths are important to be involved because they are a group that is very vulnerable to exposure to the ideology of radicalism. This paper concludes that to carry out deradicalization, the most important thing is to understand the character and ideology of radicalism movements. This strategy is important because in reality incidents of radicalism continue to occur. Even though the security forces have arrested and detained, even shot dead, the perpetrators of radicalism. This reality shows that radicalism has become a growing ideology among its followers, especially youths. By understanding the character and ideology of the radicalism movement, deradicalization programs among youths through educational institutions will be more effective. Deradicalization programs must also be carried out in a dialogical and humane manner. It is in this context that cultural dialogue involving youths across ethnicities and religions must be carried out in a sustainable manner.